The Relationship Between Suboptimal Social Networks and Postoperative Delirium: The PNDABLE Study - Tang, Xinhui; Yv, Hui; Wang, Fei; Wang, Jiahan; Liu, Siyv; Wu, Xiaoyue; Dong, Rui; Lin, Xu; Wang, Bin; Bi, Yanlin (Frontiers in Aging Neuroscience, 2022)
We investigated whether social networks are a risk factor for POD, and to verify whether different levels of intimacy in the same social relationship can affect the concentration of cerebrospinal fluid (CSF) biomarkers, such as amyloid-β(Aβ42), total tau(T-tau) and phosphorylated tau(P-tau), and the mediating role of CSF biomarkers between social network and POD in middle-aged and elderly Han people.